The situation of former adolescent self-injurers as young adults: a follow-up study - Brown, Rebecca Corinna; Kaess, Michael (BMC psychiatry, 2015)
Nonsuicidal self-injury (NSSI) in adolescence has been described as comorbid condition in affective or anxiety disorders, as well as borderline personality disorder (BPD) and is a risk factor for later suicide attempts. Prevalence rates of NSSI decline steeply from adolescence to young adulthood. Yet, to the best of our knowledge, the longitudinal development of adolescent psychiatric patients with NSSI into their young adulthood has not been investigated. The aim of this study was to assess current NSSI and psychological impairment of young adults, who had been in treatment for NSSI in their adolescence.